Association between location of out-of-hospital cardiac arrest, on-scene socioeconomic status, and accessibility to public automated defibrillators in two large metropolitan areas in Canada and France. (December 2022) - Heidet, Matthieu; Freyssenge, Julie; Claustre, Clément; Deakin, John; Helmer, Jennie; Thomas-Lamotte, Bruno; Wohl, Mathys; Danny Liang, Li; Hubert, Hervé; Baert, Valentine; Vilhelm, Christian; Fraticelli, Laurie; et al.
Abstract: Aim: To compare walking access times to automated external defibrillators (AEDs) between area-level quintiles of socioeconomic status (SES) in out-of-hospital cardiac arrest (OHCA) cases occurring in 2 major urban regions of Canada and France. Methods: This was an international, multicenter, retrospective cohort study of adult, non-traumatic OHCA cases in the metropolitan Vancouver (Canada) and Rhône County (France) regions that occurred between 2014 and 2018. We calculated area-level SES for each case, using quintiles of country-specific scores (Q5 = most deprived). We identified AED locations from local registries. The primary outcome was the simulated walking time from the OHCA location to the closest AED (continuous and dichotomized by a 3-minute 1-way threshold). We fit multivariate models to analyze the association between OHCA-to-AED walking time and outcomes (Q5 vs others). Results: A total of 6, 187 and 3, 239 cases were included from the Metro Vancouver and Rhône County areas, respectively. In Metro Vancouver Q5 areas (vs Q1-Q4), areas, AEDs were farther from (79 % over 400 m from case vs 67 %, p < 0.001) and required longer walking times to (97 % above 3 min vs 91 %, p < 0.001) cases. In Rhône Q5 areas, AEDs were closer than in other areas (43 % over 400 m from case vs 50 %, p = 0.01), yet similarly poorly accessible (85 % above 3 min vs 86 %, p = 0.79). In multivariate models, AED access time ≥ 3 min was associated with decreased odds of survival at hospital discharge in Metro Vancouver (odds ratio 0.41, 95 % CI [0.23–0.74], p = 0.003). Conclusions: Accessibility of public AEDs was globally poor in Metro Vancouver and Rhône, and even poorer in Metro Vancouver's socioeconomically deprived areas.